Carbazole functionalized new bipolar ligand for monochromatic red light-emitting europium(iii) complex: combined experimental and theoretical study. (23rd March 2017) - Rajamouli, B.; Dwaraka Viswanath, C. S.; Giri, S.; Jayasankar, C. K.; Sivakumar, V.
Abstract : Complete energy transfer observed from carbazole functionalized bipolar ligand as well as β-diketonate to Eu(iii ) ion and Eu(iii ) complex shows efficient PLQE (41.4%) with appropriate CIE color coordinates ( x = 0.64, y = 0.36). Abstract : A carbazole functionalized novel class of bipolar ligand and their corresponding β-diketonate Eu(iii ) complex was designed, synthesized and characterized successfully. The photoluminescence results show that the efficient energy transfer occurs from the ligand to the europium(iii ) center metal ion, and a narrow band red emission with apt CIE color gamut is observed. TD-DFT calculations were performed to know the energies of the singlet ( 1 S) and triplet ( 3 T) levels for the bipolar ligand and good overlap between the ligand triplet level and Eu(iii ) excited level is shown. The PL quantum yield was found to be 44.4%, and the lifetime of the complex was investigated, which is found to be 0.53 ms in chloroform solution. HOMO and LUMO energy level energies (redox reaction) were calculated from the electrochemical analysis for the Eu(iii )-complex, and the values were 5.7 and 3.0 eV, respectively. The synthesized Eu(iii ) complex was doped with polymethylmethacrylate in different percentage ratios, and it was found that the concentration variation influenced on intensity as well as symmetry. The complex is stable up to 270 °C as observed from differential scanning calorimetry-thermogravimetric analysis, which signifies that it is a promising candidate for further investigations.